Tangent Bishop spherical images of a biharmonic B-slant helix in the Heisenberg group Heis3 - Korpinar, T.; Turhan, E.; Asil, V. (Springer Int Publ Ag, 2012)
In this paper, biharmonic slant helices are studied according to Bishop frame in the Heisenberg group Heis(3), We give necessary and sufficient conditions for slant helices to be biharmonic. The biharmonic slant helices are characterized in terms of Bishop frame in the Heisenberg group Heis(3). We give some characterizations for tangent Bishop spherical images of B-slant helix. Additionally, we illustrate four figures of our main theorem.
Keywords: Biharmonic curve; Bishop frame; Heisenberg group; tangent Bishop spherical images